PENGARUH JUMLAH UANG BEREDAR M2 TERHADAP TINGKAT INFLASI DI INDONESIA PERIODE JULI 2020 - DESEMBER 2022 (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research seeks to analyze the statistical correlation between the expansion of the money supply (JUB) and the inflation rate in Indonesia from July 2020 to December 2022.  The research employs descriptive statistical analysis, incorporating measures of central tendency (mean, median, mode), location (percentiles), and dispersion (range, standard deviation, interquartile range, and ratio analysis) to elucidate the dynamics and distribution patterns of both variables.  The results demonstrate a consistent growth in the money supply over the examined timeframe, with an average of 7,409.57 trillion rupiah.  The distribution exhibited relative symmetry, indicated by a median proximate to the mean.  Conversely, inflation statistics had a right-skewed distribution, with an average inflation rate of 2.61%, but the median and mean were far lower, recorded at 1.68% and 1.42%, respectively.  Percentile study indicated that while the inflation rate was moderate and consistent in the first stages, it escalated significantly from the 70th percentile forward, culminating in a high during the last quarter of 2022.  The inflation-to-money supply ratio markedly rose throughout this period, indicating that inflationary pressure reacted to the buildup of liquidity in the economy.  These findings emphasize the need of prompt and suitable monetary policy measures to harmonize liquidity expansion with price stability, particularly during periods of economic recovery and global unpredictability.